Sensual aesthetic values ​​of women in the poetry of the pre-Islamic third class poets - ياسر الخالدي; فاطمة التميمي (آداب الكوفة, 2015)
Women's presence was felt in the third class poets ignorant; they ate each according to what he sees as the aesthetic values, and those values were distributed between sensuality and moral. The nature of the search warrant has been divided on what seemed to them from the aesthetic features, attached to each course created by the beauty of the face, eyes, hair, mouth, and others. Others have attached Bgeleta and her clothes and fragrance including added    from aesthetic values